Pengaruh Jenis Daun Pembungkus dan Isian Adonan Sagu Baikumti Terhadap Suhu dan Lama Waktu Pemanggangan Serta Sifat Organoleptik - Benyamin Essau; Yus Witdarko; Parjono Parjono; Wiyan Afriyanto Pamungkas (Faculty of Agriculture, Musamus University, 2022)
Sago Baikumti is a traditional Yaqai food made from sago wrapped in leaves and cooked by grilling. This study aims to determine the effect of the wrapping leaves and the filling type of Baikumti Sago on the length of time and temperature of grilling and the characteristics of the organoleptic properties produced. The wrapping leaves used were nibung leaves and coconut leaves, while the stuffing mixture used was venison and grated coconut. The results showed that the temperature required to ripen Baikumti sago wrapped in nibung and coconut leaves ranged from 320-380 oC and 230-320 oC, respectively. The grilling time of each type of leaf wrapper is 20 minutes and 30 minutes. The results of the organoleptic test showed that Baikumti sago wrapped in nibung leaves with both filling types was preferable to Baikumti sago wrapped in coconut leaves. The panellists preferred the texture of Baikumti sago with venison filling to Baikumti sago with grated coconut filling. Baikumti sago wrapped in nibung leaves and coconut leaves with 2 types of filler has a good appearance and was liked by the panellists.